Epidemiological Analysis of COVID-19 Patients detected by Real-Time Reverse Transcription - Polymerase Chain reaction in a Tertiary Care Biosafety Level III Laboratory, Rawalpindi - Rabia Anjum, Nadeem Ikram, Asma Nafisa, Naeem Akhtar, Rabia Anjum, Nadeem Ikram, Asma Nafisa, Naeem Akhtar (Journal of Rawalpindi Medical College, 2021)
Introduction: Unexpected eruption and global dissemination of Coronavirus disease (COVID-19) has tested the healthcare systems of both developed and developing countries. Objective: To analyze the spectrum of novel coronavirus infection in a tertiary care setup. Materials and Methods: All oropharyngeal and nasopharyngeal samples (n=7057) were collected in a viral transport medium (VTM) for qualitative analysis by a real-time reverse transcription-polymerase chain reaction (RT-PCR) machine. Positive and negative controls were applied with each batch. Positive cases were stratified into mild, moderate, severe, and asymptomatic, according to the guidelines of the National Institute of Health, Pakistan. Descriptive statistical tests were applied including percentage, chi-square tests, mean, median, and mode. P < 0.05 was counted as statistically significant. Results: Average positive test rate was 18.97% (n=1339). The maximum positivity rate (26%) of COVID-19 infection was observed in June 2020. Most of the cases (60%) belonged to Rawalpindi District, were male (n=844, 63.03%), and belonged to age group (20-40 years) and mean of 36 and age range from 2-85 years. Forty-nine percent of COVID-19 infected patients were asymptomatic and only 9.8% progressed to severe disease. Overall, the mortality rate was 159(11.87%) in RT-PCR confirmed cases. Conclusion: Average positive test rate was 18.97%. The majority of the participants belonged to the young age group (20-40 yrs.) with a range from 2 to 85 years. Forty-nine percent positive COVID-19 infected patients were asymptomatic while 9.8% had severe disease.